Exploring Servant Leadership Instrument for Social Enterprise (Cooperative) - Latiff, Aziz; Izaidin Abdul Majid,; Maizura Mohamad, (European Journal of Multidisciplinary Studies, 2017)
The purpose of this paper is to describe the development and validation of a multi-dimensional instrument to measure servant leadership in social enterprise (cooperative) context. Based on an extensive literature review, expert’s judgment and Exploratory Factor Analysis (EFA), 57 items were formulated and only 27 items yielding to five factors: doing right things, develop vision with others, democratic, develop others potential and develop community. The construct develops purposely for social enterprise (cooperative). The participants of the study consisted random sample of the cooperative’s manager in Malaysia.
Keywords: Exploring Servant Leadership Instrument for Social Enterprise (Cooperative)